A collaborative approach to care coordination: Maccabi case study - Kubů, Pavel; Kaye, Rachelle; Waksman, Mariana; Mark N. Blatt; Corrigan, T (European Journal for Biomedical Informatics, 2014)
Cost pressures, new payment models, and demographic trends are creating a global economic crisis as health systems struggle to care for an aging population of sicker patients. Funds available for healthcare are constrained, and they're being wasted by inefficient, uncoordinated healthcare services. Reflecting the importance of collaboration in caring for patients with chronic conditions, nearly 80 percent of the scoring criteria for the National Committee for Quality Assurance's (NCQA) Recognition Program for Physician Practice Connections (PPC) Patient-Centered Medical Home (PCMH) relate to information sharing and teamwork. New payment models are forcing delivery networks to share the risks and potential cost savings of caring for these patients.
Keywords: počítačová farmakoterapie; informační systémy; Information Systems; zdravotní záznamy osobní; zdravotnické informační systémy; Electronic Prescribing; Health Information Systems; elektronické předepisování; Health Records, Personal; Electronic Health Records; systémy podporující rozhodování v léčbě; Medical Order Entry Systems; Drug Therapy, Computer-Assisted; elektronické zdravotní záznamy